Monitoring dan Kontrol Suhu Berbasis Arduino dan ESP8266 Melalui Web Server - Mahdar, Fajri Hidayat; Bakri, Muh. Fajrin (Journal of Security, Computer, Information, Embedded, Network, and Intelligence System, 2024)
This study describes the use of Arduino and ESP8266 to control temperature through a web server. Arduino serves as the brain of the system that collects temperature and humidity data from sensors and controls the temperature device, while the ESP8266 acts as a link to the WiFi network and web server. This system allows users to monitor temperature conditions in real-time through a web interface. Temperature and humidity data collected by Arduino is sent to ESP8266 via serial communication, then ESP8266 uses WiFi connection to send data to web server. The web server provides a user interface that allows users to view temperature and humidity data and remotely control temperature devices. Users can send commands via the web server to activate or deactivate the temperature device as needed. The advantages of using Arduino and ESP8266 are the flexibility and connectivity offered. Arduino provides a programming environment that is easy to use and can be configured according to application needs. The ESP8266 allows a WiFi connection which allows control over a local network or the internet. In this study, the system developed was successful in efficiently controlling the temperature through a web server. Real-time monitoring of temperature and humidity data, and remote control of temperature devices. The use of Arduino and ESP8266 in temperature control via a web server opens up the potential for smart and efficient solutions in managing temperature by utilizing IoT technology.